Breakthrough infections and acceptance of COVID-19 vaccine boosters: A survey analysis - Christina W. Stevens; Stephen R. Neely; Joshua M. Scacco (Elsevier, 2023)
Objective: This Short Communication explores the effect of COVID-19 breakthrough infections (defined as a COVID-19 diagnosis after vaccination) on the willingness of previously vaccinated individuals to receive ongoing vaccine boosters. Specifically, we examine unique effects for three different breakthrough infection experiences, including the participant themselves, a close member of their family, and a friend/coworker. Methods: A representative, web-based survey of 600 adults in the state of Florida was fielded in March/April of 2022. Among the respondents, 455 had been vaccinated against COVID-19. Their responses were analyzed for this study using both descriptive and inferential statistical methods. Results: Individuals who have experienced a personal breakthrough infection are two times less likely to receive annual vaccine boosters, ceteris paribus. However, there is not a statistically significant relationship between vaccine acceptance and breakthrough infections among close family members or friends/coworkers. We also found a very strong relationship between vaccine decisions and confidence in public health guidance. Conclusion: Our findings show that confidence in public health guidelines is the most compelling determinant of vaccine acceptance, but breakthrough infections also have a significant impact on individual decision making when it comes to ongoing vaccination. Going forward, public health messaging should directly account for this correlation in order to effectively maintain vaccination levels. Innovation: The COVID-19 pandemic marked a turning point in the development and deployment of mRNA vaccines. This study contributes to innovation in health communication research by examining how breakthrough infections in these vaccinated individuals impacts ongoing booster shot acceptance. The findings of this study contribute to the nascent and ongoing development of baseline research in this area.